The relationship between knowledge management and innovation: empirical study on AUC and Mansoura University - Numair, Ashraf Mohamed (AUC Knowledge Fountain, 2012)
The purpose of this research is to examine the relationship between knowledge Management (KM) and innovation capability in two universities. They are the American University in Cairo and Mansoura University. Given the scarcity of studies that investigated these variables within the higher education context, we borrowed gold et al model that links KM to performance effectiveness in business sector and adapted it to the higher education context. According to this model, KM is seen as KM infrastructure (Culture, structure, and technology), and KM processes (k-acquisition, k-conversion, k-application, and k-protection). The findings show that AUC supersedes Mansoura University in terms of KM infrastructure, KM processes, and innovation. Also, results show that there is a significant and positive relationship between KM infrastructure, KM processes, and Innovation